Untangling Sex Dimorphisms in Coagulation: Initial Steps Toward Precision Medicine for Trauma Resuscitation. Issue 6 (June 2020) - Coleman, Julia R.; Moore, Ernest E.; Sauaia, Angela; Samuels, Jason M.; Moore, Hunter B.; Ghasabyan, Arsen; Chandler, James G.; Swope, Megan L.; Fleming, Courtney D.; Banerjee, Anirban; Cohen, Mitchell J.; Silliman, Christopher C.; et al.
Abstract : Supplemental Digital Content is available in the text